KETERAMPILAN MANAJEMEN KELAS TUTOR TERHADAP MOTIVASI BELAJAR WARGA BELAJAR PAKET C DI PKBM PELANGI KOTA AMBON - Ferdinanda Sherly Noya; Hermalina Abarua; Mirdayati Aihena; Junita Kundre; Megalina Makuku (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of tutors’ classroom management skills on the learning motivation of Package C learners at PKBM Pelangi, Ambon City. The research employed a quantitative approach with an ex-post facto design. The population and sample consisted of 45 Package C learners selected through total sampling technique. Data were collected using questionnaires with a Likert scale and analyzed using simple linear regression with SPSS 20. The results showed a positive and significant influence of tutors’ classroom management skills on learning motivation, with a t-count of 3.162 and significance value of 0.003 (<0.05). The coefficient of determination (R²) was 0.798, indicating that 79.8% of the variance in learning motivation can be explained by tutors’ classroom management skills. This study recommends that tutors continuously improve their classroom management competencies to enhance learners’ motivation in non-formal education settings.